2021
DOI: 10.5152/tud.2020.20472
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging procedure for pelvic fracture urethral injuries and recto urethral fistulas: A simplified protocol

Abstract: Objective:The urethral gap in pelvic fracture urethral injury (PFUI) is traditionally assessed using voiding cystourethrogram (VCUG) and retrograde urethrogram (RGU). Magnetic resonance imaging (MRI) is performed in complex cases. We assessed the refined "Joshi" MRI protocol to evaluate complex urethral defects after PFUI. Material and methods:A prospective study was conducted at our center from January 2018 to January 2020, involving patients aged >18 years with PFUI, suitable for MRI, and those who gave cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…Joshi et al . reported that compared with conventional MRI, using the aforementioned Joshi protocol resulted in a urethral gap length that was 0.3–1.1 cm shorter, improving consistency with urethrography results 17 …”
Section: Essential Mri Information In Pfui Patientsmentioning
confidence: 85%
See 4 more Smart Citations
“…Joshi et al . reported that compared with conventional MRI, using the aforementioned Joshi protocol resulted in a urethral gap length that was 0.3–1.1 cm shorter, improving consistency with urethrography results 17 …”
Section: Essential Mri Information In Pfui Patientsmentioning
confidence: 85%
“…2c). The most dreaded complication of DAU is rectal injury 17 . Knowing the positional relationship between the rectum and the urethra based on MRI before urethroplasty might help prevent rectal injury.…”
Section: Essential Mri Information In Pfui Patientsmentioning
confidence: 99%
See 3 more Smart Citations